"The Image of Women in Modern Arabic Poetry: Between Liberation and Tradition: A Study of the Poetry of Fadwa Tuqan and Nazik al-Malaika" - Ass.Lect .Najm Abdei Turki (Journal of College of Education, 2026)
The poets Fadwa Tuqan and Nazik al-Mala’ika are considered two of the pioneering poets of the modern era. Their rise coincided with historical events in our region, which had repercussions on social life in general and on women in particular. Therefore, this study aims to analyze the image of women in modern Arabic poetry through the models of the Palestinian poet Fadwa Tuqan and the Iraqi poet Nazik al-Mala’ika, and to reveal the manifestations of liberation from tradition in portraying women as an active and creative agent. The study adopts an integrative analytical approach that combines textual and contextual treatment, analyzing poetic models in light of their social, psychological, and historical contexts. The study concludes that Tuqan and al-Mala’ika represented a qualitative shift in the portrayal of women by embodying the creative voice of women that reflects their personal and national concerns and contributes to the development of both poetic form and content.